1989
DOI: 10.1139/z89-421
|View full text |Cite
|
Sign up to set email alerts
|

Nucleated red cell function: metabolism and pH regulation

Abstract: The full extent and apportionment of aerobic and anaerobic contributions to energy transduction for membrane pumps associated with cellular pH regulation are very poorly understood. One way of approaching this problem at the cellular level is by using the nucleated erythrocyte as a model cell. Indeed, the aerobic and anaerobic capacity of salmonid erythrocytes and their β-adrenergic mediated pH regulation offers a model "pH regulating system" for examining cellular strategies of response to acute and (or) chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Valet al (1994) showed that nucleotide triphosphate levels were increased in the erythrocytes of anemic fish. These increased levels of high energy phosphates may result in a decrease of pHi in fish red cells (Boutilier and Ferguson 1989).…”
Section: Plasma Catecholaminesmentioning
confidence: 99%
“…Valet al (1994) showed that nucleotide triphosphate levels were increased in the erythrocytes of anemic fish. These increased levels of high energy phosphates may result in a decrease of pHi in fish red cells (Boutilier and Ferguson 1989).…”
Section: Plasma Catecholaminesmentioning
confidence: 99%
“…In recent years, research has focused intensively on two model systems, the teleost red blood cell (rbc) and the hepatocyte. The interaction of catecholamines with the rbc results in enhancement of blood oxygen transport (Nikinmaa and Tufts 1989;Boutilier and Ferguson 1989;Fievet and Motais 1991;Randall and Perry 1992; Thomas and Perry 1992) while the interaction of catecholamines with hepatocytes enhances the metabolic potential of the animal owing to mobilization of glucose (e.g. Ottolenghi et al 1985Ottolenghi et al , 1986Brighenti et al 1987b;Janssens and Lowrey 1987;Sheridan 1988;Mommsen et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Second, adrenergic stimulation of 2,4-DNP treated brown trout red cells did not cause changes in the chloride distribution ratio because intracellular alkalinization (and a consecutive increase in bicarbonate concentration) was prevented by the protonophore. Owing to the adrenergically stimulated sodium influx, the sodium pump is stimulated and the intracellular ATP concentration decreases (for example, see Boutilier and Ferguson 1989).…”
Section: Teleost Red Cells: Adrenergically Stimulated Sodiumproton Exmentioning
confidence: 99%